1991
DOI: 10.1007/bf00587633
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic neuropathy and survival in diabetes mellitus: effects of pancreas transplantation

Abstract: Summary. Cardiorespiratory reflexes were studied during slow breathing and a Valsalva maneuver in 232 Type 1 (insulin-dependent) diabetic subjects. At 1 to 7 years follow-up, death occurred in 23.4% of 175 patients with abnormal reflexes and in 3.5% of 57 patients with normal reflexes. The mortality rates of diabetic subjects with abnormal reflexes were 17% at 2.5 years, 33% at 5 years and 40% at 7 years, significantly higher than for patients with normal reflexes (4.6%, 4.6% and 13.8%). Among patients with ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 35 publications
(35 reference statements)
1
21
0
Order By: Relevance
“…Conflicting results have been reported from renal and pancreatic-transplanted diabetic patients [21][22][23][24], however, improvement has been found after a follow-up period of 4ϩ years [22,23] therefore the follow-up of 17 months in the present investigation may be too short.…”
Section: Discussionmentioning
confidence: 64%
“…Conflicting results have been reported from renal and pancreatic-transplanted diabetic patients [21][22][23][24], however, improvement has been found after a follow-up period of 4ϩ years [22,23] therefore the follow-up of 17 months in the present investigation may be too short.…”
Section: Discussionmentioning
confidence: 64%
“…Cardiac autonomic neuropathy (CAN) is a serious complication of diabetes, which also associates with increased CVD risk and mortality (38). The loss of heart rate (HR) variability, an index of CAN, is an independent predictor of mortality after an acute myocardial infarction in nondiabetic (ND) subjects (3) and in patients with type 1 and type 2 diabetes (60).…”
mentioning
confidence: 99%
“…This is an important finding since patients with autonomic neuropathy frequently have hypoglycaemia unawareness. In addition, many authors showed that abnormalities in autonomic testing frequently are associated with high rates of mortality in diabetic patients [3,15,16,18]. Interestingly, another study showed that thinly myelinated and unmyelinated nerve fibres in patients with diabetic neuropathy seem to improve less or at least at a slower rate than myelinated fibres after pancreas transplantation [11,17,25].…”
Section: Discussionmentioning
confidence: 97%